Pembahasan Defence Cooperation Agreement Indonesia - Singapura oleh DPR dan Pemerintah Indonesia dan Implikasinya bagi Teori Birokratik Politik - Sari, Angguntari C.; D, Mira Permatasari; Syawfi, Idil (Parahyangan Center for International Studies, 2013)
Abstract: This paper aims to examine the extent to which the internal discussion of the Defence andCooperation Agreement between Indonesia and Singapore consistent with the bureaucratic politicstheory. Using the null hypotesis and process tracing methods, this paper tests the bureaucratic politictheory, which was first introduced in the foreign policy studies by Graham Allison and PhilipZelikiow. Specifically, this paper asks the following questions: Who are the foreign policy makers inIndonesia with regards to the faith of DCA? What are their stances toward the future of DCA? Howdoes each decision makers advance their own opinion on this matter? What influence their stance?Does the final outcome reflect each actors initial preference over the outcome? Based on the paperscontent and other authors observation, this paper argues that the internal discussion regarding thefuture of DCA is not entirely consistent with the argument made by Allison and Zelikow inbureuacratic politics theory. .Keywords : bureaucratic politic, foreign policy, Indonesia foreign policy